Gynoecial ontogeny of Anthurium: contributions for floral developmental studies in Araceae (Alismatales) - Poli, Leticia Peres [UNESP]; Temponi, Livia Godinho; Coan, Alessandra Ike [UNESP] (Canadian Science Publishing, Nrc Research Press, 2015)
Studies on floral development have widened the knowledge on the floral morphology of Araceae, particularly in genera delimited through classical taxonomic treatments. In Pothoideae, floral ontogenetic studies are limited to some representatives of Pothoidium Schott and Pothos L. and only one species of Anthurium Schott, with no focus on gynoecium. This background reveals a lack of ontogenetic data on the largest genus in the clade. This paper presents gynoecial ontogeny of species circumscribed in different sections of Anthurium, describes gynoecial developmental patterns, and evaluates the relevance of ontogenetic characteristics in the taxonomy of the sections studied. New data for the Araceae include the recognition of four floral developmental phases, the carpellary nature of the ovarian septum, and the development of the symplicate and synascidiate zones of the gynoecium. The apical septum described in Anthurium scandens (Aubl.) Engl. is first reported for the genus in this study. We also highlight the importance of these ontogenetic data as new information for the Pothoideae within Araceae and to understand the notable phases of floral development in the reproductive biology of Anthurium.
Keywords: Apical septum; Gynoecium; Ovarian septum; Pothoideae